A cross-sectional study to assess impact of COVID-19 infection amongst patients with chronic kidney disease - Mahajan, Harshalkumar N.; Chavhan, Smita S.; Gokhale, Chinmay; Adsul, Balkrishna B.; Kumbhar, Maharudra; Ingale, Aniket (International Journal Of Community Medicine And Public Health, 2021)
Background: In December 2019, a series of unknown origin cases of acute respiratory illness occurred in Wuhan, Hubei Province, China. Although diffuse alveolar damage and acute respiratory failure were the main features of COVID-19, the involvement of other organs needed to be explored. After lung infection, the virus may enter the blood, accumulate in the kidney, and cause damage to resident renal cells. Hence, this study was planned to analyze the potential impact of this pandemic of COVID-19 amongst the chronic kidney disease (CKD) patients. Methods: Cross-sectional observational study was conducted at Seven Hills Dedicated Covid-19 hospital, Andheri, Mumbai. Data was collected from hospital records of CKD patients admitted in the study duration. Results: This study was conducted on 310 patients. Mean age was 53.33+14.21 years, and 191 (61.6%) of patients were male while mean duration of hospitalization was 16.78+10.31. Majority of the patients presented with symptoms like fever 80%, breathlessness 61.3%, and co-morbidities like Diabetes Mellitus 65.5% followed by Hypertension 61.8%. Patients (15.5%) over age of 60 years tested swab report positive for more than 5 times. Recovery rate being 76.1% while mortality rate found to be 23.87%. Conclusions: Early detection and effective intervention may help to reduce deaths among CKD patients with COVID-19.